Trichomonas vaginalis infection and the diagnostic significance of detection tests among Ghanaian outpatients - Richard Harry Asmah; Rita Ofosuaa Agyeman; Noah Obeng-Nkrumah; Harriet Blankson; Georgina Awuah-Mensah; Momodou Cham; Listowell Asare; Patrick Ferdinand Ayeh-Kumi (BMC, 2018)
Abstract Background There is little data on Trichomonas vaginalis infection in Ghana. This study evaluated the prevalence of trichomoniasis using different diagnostic methods and determined the risk factors for infection in patients. Methods A structured questionnaire was administered. Vaginal swabs, urethral swabs and urine specimens were obtained from consenting patients; and the samples processed following standard protocols. The presence of T. vaginalis was determined using wet mount microscopy and polymerase chain reaction (PCR) as gold standard. We also assessed the diagnostic performance the JD's Trichomonas V® rapid antigen test to inform clinical practice. Results The PCR assay detected T. vaginalis positivity in 64 of 150 patients (42.6, 95%CI:35.0, 50.6) including all positive samples of wet mount microscopy and JD's Trichomonas V® test. Wet mount microscopy showed low sensitivity (31.6%), high specificity (100%), moderate positive predictive value (75.0%), moderate positive likelihood ratio (3.0), and weak agreement (Cohen's kappa, 0.283) with PCR assay. The JD's Trichomonas V® test displayed lower sensitivity (25.0%), specificity (83.3%), and weaker measure of agreement (Cohen's kappa, 0.233) with PCR. In multivariate analysis, the strongest independent predictor for T. vaginalis was female gender [adjusted odds ratio (AOR), 24.89; 95% confidence interval (CI): 10.58, 51.21; P-value< 0.001]. Knowledge of STI showed a protective effect against infection with the parasite (AOR, 0.13; 95%CI: 0.07, 0.29; P-value< 0.017). Conclusion The sensitivity of wet mount microscopy was low for T. vaginalis screening in our region. The JD's Trichomonas V® test should not be considered as an alternative test. We recommend mandatory PCR assay for confirmation of negative wet mount results.